2017
DOI: 10.1002/hyp.11357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temporal scales and space mismatches on the TRMM 3B42 v7 precipitation product in a remote mountainous area

Abstract: The accurate measurement of precipitation is essential to understanding regional hydrological processes and hydrological cycling. Quantification of precipitation over remote regions such as the Tibetan Plateau is highly unreliable because of the scarcity of rain gauges. The objective of this study is to evaluate the performance of the satellite precipitation product of tropical rainfall measuring mission (TRMM) 3B42 v7 at daily, weekly, monthly, and seasonal scales. Comparison between TRMM grid precipitation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Previous studies also reported TRMM's unsatisfactory results when monitoring extreme rainfall [24,50]. One possible reason is that the PR and TMI sensors embedded in TRMM were not sensitive to detect light or heavy rainfall, while the GPM DPR and GMI were better at detecting light and solid rainfall events [16,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also reported TRMM's unsatisfactory results when monitoring extreme rainfall [24,50]. One possible reason is that the PR and TMI sensors embedded in TRMM were not sensitive to detect light or heavy rainfall, while the GPM DPR and GMI were better at detecting light and solid rainfall events [16,51].…”
Section: Discussionmentioning
confidence: 99%
“…A grid-to-point approach (NN method) was also used to compare between the point-based rain gauges and pixel-based SPPs. However, attention should be given to the errors that may be induced after resampling and undertaking grid-to-point techniques due to scale mismatch issues, and the errors that have already existed due to fundamentally different measurements between rain gauges and SPPs [15,33,51]. Moreover, various interpolation methods and grid-to-point techniques can also produce different evaluation results.…”
Section: Discussionmentioning
confidence: 99%
“…The precipitation distribution in Figure 8b showed an underestimation of satellite estimates when the rainfall rates were either less than 0.5 mm/day or greater than 25 mm/day. Ebrahimi et al [41] pointed out that satellite sensors are not sensitive to light rainfall and heavy rainfall, which might lead to unsatisfactory monitoring of extreme rainfall. The IMERG v5 product, with relatively high POD and CSI, showed better performance in precipitation detection of the Huaihe River basin.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that IMERG v5 was more suitable for characterizing the spatial variation of precipitation. However, it is worth pointing out that the accuracy of satellite precipitation at daily scale is still poor, which limits the application of satellite precipitation products to some extent [41]. Xu et al [40] found that the performance of GPM and TRMM strongly depends on topography and rainfall intensity over the southern Tibetan Plateau.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation